(untitled) (Research, Society and Development, 2021)
Vermiculite is an expansive material that can be used for crop production. However, information about the use of vermiculite in vegetable production is scarce. Thus, this study’s objective was to evaluate the effects of vermiculite levels incorporated into the soil (Red Latosol Dystrophic) for beet (Beta vulgaris L.) crop production. The experiment was performed during spring using the beet cultivar ’Early Wonder Tall Top’ and 0, 2, 4, 6, 8, and 10 t∙ha-1 of vermiculite incorporated into the soil before seedling planting. The increase of the vermiculite doses caused a linear decrease of the fresh root and leaf weight. The yield reductions were due to the great water holding capacity of the vermiculite and the consequent high incidence of cercosporiosis (Cercospora beticola Saac).